Perinatal Survival of a Fetus with Intestinal Volvulus and Intussusception: A Case Report and Review of the Literature - Ohuoba, Esohe; Fruhman, Gary; Olutoye, Oluyinka; Zacharias, Nikolaos (American Journal of Perinatology Reports, 2013)
Fetal intestinal volvulus is a rare life-threatening condition. Late diagnosis of volvulus contributes to high rate of morbidity and mortality. It has variable degrees of presentation and survival. Intrauterine volvulus may be complicated by intestinal atresia due to ischemic necrosis. To our knowledge, there are three reported cases of term fetal demise. We report a case of fetal intestinal volvulus with perinatal survival of the largest term infant described with this complication to date. The volvulus was associated with type 3A jejunal atresia and intestinal pathology was noted on prenatal ultrasound. The infant was born via urgent cesarean delivery at 376/7 weeks of gestation and underwent emergent exploratory laparotomy with resection of small bowel and primary end-to-end anastomosis. Intrauterine intestinal volvulus may be suspected on prenatal ultrasound but only definitively diagnosed postnatally. Signs of fetal distress and volvulus are rarely associated with reports of survival in the term fetus. We review reported cases of prenatally suspected volvulus in infants documented to survive past the neonatal period. As fetal volvulus and most intestinal atresias/stenoses manifest during the third trimester, we recommend that the limited fetal anatomical survey during growth ultrasounds at 32 to 36 weeks routinely include an assessment of the fetal bowel.
Keywords: fetal intestinal volvulus; perinatal mortality; intussusception; intrauterine volvulus